2022
DOI: 10.1242/jcs.259178
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated flotillins and sphingosine kinase 2 derail AXL vesicular traffic to promote epithelial-mesenchymal transition

Abstract: Altered endocytosis and vesicular trafficking are major players during tumorigenesis. Flotillin overexpression, a feature observed in many invasive tumors and identified as a marker of poor prognosis, induces a deregulated endocytic and trafficking pathway called upregulated flotillin-induced trafficking (UFIT). Here, we found that in non-tumoral mammary epithelial cells, induction of the UFIT pathway promotes epithelial-to-mesenchymal transition (EMT) and accelerates the endocytosis of several transmembrane r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The Axl receptor is a key downstream regulator that is required for many malignant tumors to migrate and spread [13][14]. Therefore, Axl receptor overexpression is closely associated with cancer initiation and development [15].…”
Section: Axl Receptor In Emtmentioning
confidence: 99%
“…The Axl receptor is a key downstream regulator that is required for many malignant tumors to migrate and spread [13][14]. Therefore, Axl receptor overexpression is closely associated with cancer initiation and development [15].…”
Section: Axl Receptor In Emtmentioning
confidence: 99%
“…Researchers have observed that its expression increases in subjects with Down syndrome (which are prone to develop earlier onset dementia) and AD patients [ 74 , 76 ]. Furthermore, flotillins participate in axonal regeneration [ 77 ], membrane and vesicular trafficking [ 78 ], cell migration, signal transduction, and endocytosis, which depends on the levels of phosphorylation and S-palmitoylation of the protein [ 78 , 79 , 80 ].…”
Section: Lipid Raftsmentioning
confidence: 99%
“…Due to their membrane binding on the one hand and direct binding of numerous proteins on the other, homo-and hetero-oligomers of flotillins can serve as scaffolds enabling the assembly of multiprotein complexes involved in signal transduction, clathrin-/caveolin-independent endocytosis of plasma membrane proteins, and cytoskeleton remodeling [29][30][31][32][33][34]. Importantly, a growing set of recent data indicates that flotillins can also associate with endo-membranes, including the Golgi apparatus and the endo-lysosomal compartment, to take part in protein trafficking and thereby affect signaling of diverse plasma membrane receptors [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%